Task-oriented exercise effects on walking and corticospinal excitability in multiple sclerosis: protocol for a randomized controlled trial - Zahra Moslemi; Eduardo A. Toledo-Aldana; Bruce Baldwin; Sarah J. Donkers; Janice J. Eng; Prosanta Mondal; Julia O. Totosy de Zepetnek; Josef Buttigieg; Michael C. Levin; Cameron S. Mang (BMC, 2023)
Abstract Background Multiple sclerosis (MS) is a degenerative disease of the central nervous system (CNS) that disrupts walking function and results in other debilitating symptoms. This study compares the effects of 'task-oriented exercise' against 'generalized resistance and aerobic exercise' and a 'stretching control' on walking and CNS function in people with MS (PwMS). We hypothesize that task-oriented exercise will enhance walking speed and related neural changes to a greater extent than other exercise approaches. Methods This study is a single-blinded, three-arm randomized controlled trial conducted in Saskatchewan, Canada. Eligible participants are those older than 18 years of age with a diagnosis of MS and an expanded Patient-Determined Disease Steps (PDDS) score between 3 ('gait disability') and 6 ('bilateral support'). Exercise interventions are delivered for 12 weeks (3 × 60-min per week) in-person under the supervision of a qualified exercise professional. Interventions differ in exercise approach, such that task-oriented exercise involves weight-bearing, walking-specific activities, while generalized resistance and aerobic exercise uses seated machine-based resistance training of major upper and lower body muscle groups and recumbent cycling, and the stretching control exercise involves seated flexibility and relaxation activities. Participants are allocated to interventions using blocked randomization that stratifies by PDDS (mild: 3-4; moderate: 5-6). Assessments are conducted at baseline, post-intervention, and at a six-week retention time point. The primary and secondary outcome measures are the Timed 25-Foot Walk Test and corticospinal excitability for the tibialis anterior muscles determined using transcranial magnetic stimulation (TMS), respectively. Tertiary outcomes include assessments of balance, additional TMS measures, blood biomarkers of neural health and inflammation, and measures of cardiorespiratory and musculoskeletal fitness. Discussion A paradigm shift in MS healthcare towards the use of "exercise as medicine" was recently proposed to improve outcomes and alleviate the economic burden of MS. Findings will support this shift by informing the development of specialized exercise programming that targets walking and changes in corticospinal excitability in PwMS. Trial registration ClinicalTrials.gov, NCT05496881, Registered August 11, 2022. https://classic.clinicaltrials.gov/ct2/show/NCT05496881 . Protocol amendment number: 01; Issue date: August 1, 2023; Primary reason for amendment: Expand eligibility to include people with all forms of MS rather than progressive forms of MS only.